Tomada de decisão em processos administrativos da Guarnição Aeronáutica de Santa Maria – RS: uma aplicação do processo de raciocínio da Teoria das Restrições - Silva, Rodrigo Marques da (2022)
This research made an application of the Theory of Constraints' Thinking Process for the decision making in administrative processes in a unit of the Brazilian Air Force. It approaches the organizations' difficulties in dealing with non-structuralized problems in the setting of Brazil's Public Administration. From the bibliographic survey of published studies in scientific papers, this research intended to propose solutions at a strategic level in order to help the decision making in administrative acquisition processes of the unit of the Brazilian Air Force of Santa Maria, RS. The research method used was a qualitative approach through focused group meetings with the intention of making a case study of analytic character, the procedure of data research and analysis being composed of three steps, representative of an application of the Theory of Constraints' Thinking Process. Among the main results, problems related to bad leading of the acquisition processes were identified, resulting in errors in the elaboration of documents that compose the processes, associated with low capacity of human resources at the Planning Teams motivated by factors such as high staff turnover, lack of qualification at the administrative area and prioritization of operational activities in detriment of the elaboration of the proper documents of the process, causing delays and reworks by those involved. The problems' solution measures proposed were actions envisioning the headcount capacitation, improvement of the standardization and guidance for the elaboration of documents, as well as specific advisement by military with deeper knowledge of the topic of public acquisitions. Lastly, it is presented an action plan to be utilized by the public managers, in order to improve the execution of the acquisition processes in the setting of BASM.